IMPLEMENTASI PROGRAM EKSTRAKURIKULER KEAGAMAAN DALAM PEMBENTUKAN KARAKTER MODERASI BERAGAMA SISWA DI MA AL ISHLAH LAMPUNG SELATAN - Adib, Abdul (UNISAN JURNAL, 2026)
Islamic Religious Education (PAI) plays a vital role in tackling the challenges of extremist ideology and strengthening social cohesion. This research is motivated by the urgency of instilling an inclusive and balanced Religious Moderation Character in madrasah students. The main objective is to analyze the implementation of religious extracurricular programs and identify their contribution to shaping the four dimensions of religious moderation character among students at MA Al Ishlah Lampung Selatan. The study adopted a qualitative approach with a descriptive case study design. Data was collected through in-depth interviews, participant observation, and documentation study, and then analyzed using the Miles and Huberman model. The results indicate that the implementation of religious extracurricular programs—namely Thematic Fiqh Studies (cognitive), Intensive Tadarrus (spiritual), and Religious Social Service (practical action)—is carried out synergistically and in an integrated manner. This implementation proved to contribute significantly and holistically to the formation of religious moderation character, particularly in the dimensions of Tolerance, Anti-Violence, and Cultural Acceptance. The conclusion affirms that the effectiveness of shaping religious moderation character in madrasah is determined by the Integrated Tri-Dimensional Implementation Model, which combines intellectual, spiritual, and social aspects. This model successfully shifts moderation values from mere knowledge to behavioral habituation.